2018
DOI: 10.4102/apsdpr.v6i1.175
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the causes of poverty on economic growth in Nigeria

Abstract: Background: This article examined the effect of poverty on economic growth in Nigeria because it was discovered that the existing literature has not holistically battle against the worsening scourge of poverty in Nigeria. Aim:The article specifically examined the relationship between poverty and economic growth, the determinants of economic growth and poverty from 1980 to 2013. Setting:The article is structured into five sections which include introduction, literature review, methodology, discussion of results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In terms of Head Count Ratio, the relationship between GDP and poverty was found to be deterministic because for each value of the independent variable (GDP growth rate) there is one and only one corresponding value of dependent variable (HCR). In Nigeria, Omoniyi (2018) examined the relationship between poverty and economic growth, the determinants of economic growth and poverty from 1980 to 2013 using an error correction model to analyse the time series data. The study revealed that economic growth has a negative and significat relationship with poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of Head Count Ratio, the relationship between GDP and poverty was found to be deterministic because for each value of the independent variable (GDP growth rate) there is one and only one corresponding value of dependent variable (HCR). In Nigeria, Omoniyi (2018) examined the relationship between poverty and economic growth, the determinants of economic growth and poverty from 1980 to 2013 using an error correction model to analyse the time series data. The study revealed that economic growth has a negative and significat relationship with poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this conduct has a cause and effect relationship with many other socioeconomic indicators, such as poverty, in its monetary and multidimensional aspects. That is why many authors such as Gupta et al (2002), Chetwynd et al (2003), Ndikumana (2006), andOmoniyi (2018), among others, have focused on this issue.…”
Section: Corruption Poverty and Causalitymentioning
confidence: 99%
“…As National Bureau of Statistics (2010) puts it, the proportion of Nigerians living in poverty is increasing every year despite the fact that Nigerian economy is paradoxically growing. On the other hand, poverty is an obstacle or limitation to economic growth in Nigeria (Omoniyi, 2018).…”
Section: The Poverty Debacle In Nigeriamentioning
confidence: 99%